Histological and Immunological Study of Daily Supplement of Aqueous extract of Thymus vulgaris Leaf in Mice Challenged with Vibrio alginolyticus - Ali. M. Al-Dahbi (Journal of Global Pharma Technology, 2019)
The aim of current study was evaluation the potential effects of daily supplement of aqueous extract of thymus vulgaris leaf on immunity system and some of total serum proteins performances in mice was challenged with V. alginolyticus, a total of 20 mice was divided into four group, group I:(Normal saline), group II: injected subcutenously V. alginolyticus, group III administrated orally for 14 day with 400µgkg of aqueous extract Thymus vulgaris leaf. Finally group IV injected subcutenously with V.alginolyticus and administrated orally for 14 day with 400 µg/kg of aqueous extract Thymus vulgaris leaf. The results of phagocytic activity reported there were significant differences (P≤0.05) between group IV (3.90±0.24) and (2.77±0.24); group II (2.65±0.24), while there was no highly significant difference (P≤0.05) between groups II, group III. In other hand lymphocytes proliferation results were revealed group III, group IV (0.380±0.020, 0.400±0.08) were recorded highly significant differences with Group II (2.65±0.24).In addition, the total serum proteins were showed the highest value was recorded in group III and group IV at day 10 and day 14 with highly significant differences (P≤0.05), Furthermore For delayed type hypersensitivity (DHT), the results were revealed group IV had the highest value after 48, 72 hr, (3. 6±0.33) and recorded a highly significant difference (P≤0.05) with group III, group II after 48, 72 hr. Finally the histopathological examinations of small intestines were showed changes in group II like losing of mucous membranes, damaging in villa, moreover in group IV there were presence of inflammatory cells in damaged area also there were villi partially damaged. This study was revealed depending on the results, the daily supplement of aqueous extract thymus vulgaris leaf (400 µg /kg) had positive effects on the immune response, total serum protein, and showed positive effects in histological examinations through protection the small intestine from V. alginolyticus invasion.Keywords: Aqueous extract of Thymus vulgaris leaf, Histological changes, Immunological response, V.alginolyticus.